Rhabdomyosarcoma of urethra a rare case presentation - Thapa, N.; Thapa, B.B.; Bhandari, B.B.; Hamal, B.K. (Journal of Society of Surgeons of Nepal, 2016)
Rhabdomyosarcoma of urethra is extremely a rare presentation. Only few cases were found documented and published in literature. We present a case of rhabdomyosarcoma in the urethra presenting with history of gross heamaturia. Diagnosis of this case was made cystoscopically and confirmed by histopathologically. Complete radical surgery followed by six cycle chemotherapy was given in this case.